Silane-modified urethane acrylate oligomer and ultraviolet curable coating composition comprising same

By preparing a specific ratio of silane-modified urethane acrylate oligomer and UV-curable coating composition, the adhesion and weather resistance problems of the coating composition on transparent/black PC materials were solved, and the stability and performance of the coating composition on automobile headlights and electric vehicle radiator grilles were improved.

CN120826425APending Publication Date: 2025-10-21KCC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480017268.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-20
Filing Date
2024-03-18
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Existing coating compositions fail to provide adequate adhesion and weather resistance on transparent/black PC materials, resulting in a deviation in the curing balance, especially in the stability and performance issues of the coating compositions on automotive headlights and electric vehicle radiator grilles.

Method used

A silane-modified urethane acrylate oligomer prepared from an acrylate monomer having a hydroxyl group, a silane monomer having an isocyanate group, and a silane monomer having an alkoxy group is used in combination with an ultraviolet-curable coating composition, and the molecular weight and content ratio are optimized to improve the crosslinking density and structural stability of the coating film.

Benefits of technology

It achieves excellent adhesion and weather resistance on black PC materials and transparent/black PC materials, ensures the curing stability and excellent performance of the coating composition, and is suitable for hard coating of automobile headlights and electric vehicle radiator grilles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005583194980000051
    Figure BDA0005583194980000051
  • Figure BDA0005583194980000091
    Figure BDA0005583194980000091
  • Figure BDA0005583194980000092
    Figure BDA0005583194980000092
Patent Text Reader

Abstract

The present invention relates to an ultraviolet-curable coating composition having excellent curing stability, adhesiveness and weather resistance, and a silane-modified urethane acrylate oligomer suitable for the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an ultraviolet curing coating composition having excellent curing stability, adhesion and weather resistance and a silane-modified urethane acrylate oligomer applicable thereto. Background Art

[0002] Automobile headlights (front lamps) illuminate the road ahead for safe nighttime driving. They are typically made of materials with excellent transparency, impact resistance, and formability, such as plastics, particularly polycarbonate (PC). However, PC materials lack scratch resistance, weather resistance, and chemical resistance, so to compensate for these shortcomings, they are coated with coating compositions. Research and development efforts are ongoing to provide coating compositions with superior physical properties. As an example, Korean Patent No. 10-0199908 discloses a coating composition using a multifunctional urethane acrylate oligomer. However, existing coating compositions fail to provide sufficient levels of scratch resistance, weather resistance, and chemical resistance.

[0003] Meanwhile, transparent PC lenses, made solely of transparent PC, have been primarily used in the past. However, recent automotive design trends have led to a growing demand for dual-color transparent / black lenses, achieved by co-molding transparent PC with black PC. Such transparent / black PC materials can exhibit variations in thermal conductivity, heat energy, and UV energy absorption. This results in variations in the curing balance of the coating composition under the same curing conditions, leading to reduced adhesion and weather resistance. Therefore, there is a need for a coating composition that exhibits excellent adhesion and weather resistance when applied to transparent / black PC materials.

[0004] Furthermore, with the commercialization of electric vehicles, the materials used for automotive radiator grilles are also changing. Furthermore, as the colors of electric vehicle radiator grilles diversify to black, gray, and other colors, UV-curable hard coatings are required to stabilize their physical properties, such as curing stability, adhesion, and weather resistance, on black materials. Summary of the Invention

[0005] (Problems to be solved by the invention)

[0006] The present invention provides an ultraviolet curable coating composition having excellent curing stability, adhesion and weather resistance, and a silane-modified urethane acrylate oligomer applicable thereto.

[0007] (Measures taken to resolve the problem)

[0008] The present invention provides a silane-modified urethane acrylate oligomer obtained from an acrylate monomer having a hydroxyl group, a silane monomer having an isocyanate group, and a silane monomer having an alkoxy group, and an ultraviolet curable coating composition containing the same.

[0009] (Effects of the Invention)

[0010] The UV-curable coating composition according to the present invention exhibits excellent curing stability, adhesion, and weather resistance, making it suitable for use as a coating composition for hardening coatings on automotive headlights. In particular, the UV-curable coating composition of the present invention exhibits excellent adhesion and weather resistance on black PC materials and exhibits optimal curability under UV light, providing excellent adhesion and weather resistance when applied to both black PC materials and transparent / black PC materials. DETAILED DESCRIPTION

[0011] The present invention will be described below. However, the present invention is not limited to the following content. As needed, each component can be variously deformed or selectively mixed. Therefore, it should be understood that all changes, equivalents or substitutes included in the thought and technical scope of the present invention are encompassed.

[0012] The "number average molecular weight" and "weight average molecular weight" used in this specification are measured by conventional methods known in the art, for example, they can be measured by gel permeation chromatography (GPC). "Viscosity" is measured by conventional methods known in the art, for example, it can be measured using a Brookfield viscometer at room temperature (25°C).

[0013] The UV-curable coating composition according to the present invention comprises a silane-modified urethane acrylate oligomer. The UV-curable coating composition may further comprise a polyurethane acrylate oligomer, an acrylate monomer, a photoinitiator, an organic solvent, and, if necessary, one or more additives commonly used in the art, such as a UV absorber, a UV stabilizer, a flame retardant, a leveling agent, and a defoaming agent.

[0014] Silane-modified urethane acrylate oligomer

[0015] The ultraviolet curable coating composition of the present invention contains a silane-modified urethane acrylate oligomer. The silane-modified urethane acrylate oligomer imparts excellent adhesion to the coating composition, particularly to black PC materials and excellent durability.

[0016] The number average molecular weight of the silane-modified urethane acrylate oligomer is 500 to 10,000 g / mol, for example, 1,000 to 8,000 g / mol, and the acrylic acid equivalent is 100 to 1,000 g / eq, for example, 200 to 700 g / eq. When the number average molecular weight and the acrylic acid equivalent are within the aforementioned range, the intersolubility with the resin composition is excellent and the crosslinking density of the coating film is improved, thereby improving mechanical properties, appearance, and weather resistance. When the number average molecular weight is less than the aforementioned range, the viscosity is low, thereby causing problems such as reduced adhesion and gloss of the coating film. When the number average molecular weight exceeds the aforementioned range, the coating film hardness increases and the elasticity of the coating film decreases due to the increase in molecular weight, resulting in cracks, thereby causing problems such as reduced appearance and scratch resistance. When the acrylic acid equivalent is less than the aforementioned range, the crosslinking density and curing reactivity of the coating film decrease, resulting in reduced adhesion. When it exceeds the aforementioned range, the hardness of the coating film increases, causing the coating film to become brittle, resulting in reduced elasticity and deterioration of appearance.

[0017] The silane-modified urethane acrylate oligomer has a solids content of 30 to 50%, for example, 35 to 45%, and a viscosity (25°C) of 5 to 100 cps, for example, 10 to 80 cps. If the solids content is less than the aforementioned range, the curing reactivity may be reduced due to the reduced solids content of the coating. If the solids content exceeds the aforementioned range, the workability of the coating may be impaired, resulting in a reduced appearance. If the viscosity is less than the aforementioned range, the viscosity is too low, resulting in poor coating workability and storage stability, which may reduce the adhesion and chemical resistance of the coating film. If the viscosity exceeds the aforementioned range, the workability of the coating may be impaired and the crosslinking density may be significantly increased, which may reduce the elasticity, appearance, and processability of the coating film.

[0018] The silane-modified urethane acrylate oligomer may be prepared using a composition comprising an acrylate monomer having a hydroxyl group, a silane monomer having an isocyanate group, and a silane monomer having an alkoxy group.

[0019] Based on the total weight of the composition, the composition includes 10 to 33 weight percent, for example, 15 to 30 weight percent, of an acrylate monomer having a hydroxyl group; 3 to 12 weight percent, for example, 5 to 10 weight percent, of a silane monomer having an isocyanate group; and 7 to 35 weight percent, for example, 10 to 30 weight percent, of a silane monomer having an alkoxy group. When the contents of the three monomers are within the above ranges, appropriate siloxane bonds are formed, resulting in excellent structural stability and increased miscibility with materials, which in turn improves the adhesion and durability of the coating film.

[0020] If the content of the hydroxyl group-containing acrylate monomer is less than the aforementioned range, the number of hydroxyl groups is small, resulting in reduced reactivity and, consequently, reduced durability during coating film production. If the content exceeds the aforementioned range, the number of hydroxyl groups increases, causing the coating film to become brittle, thereby reducing elasticity and, as a result, reducing the coating film's appearance, gloss, and scratch resistance. If the content of the isocyanate group-containing silane monomer is less than the aforementioned range, the number of siloxane bonds is small, resulting in a reduced crosslinking density and, consequently, reduced adhesion, gloss, and durability of the coating film. If the content exceeds the aforementioned range, the increased molecular weight of the silane leads to increased reactivity with water, causing hydrolysis, which reduces the coating's storage properties and, as a result, reduces the coating film's appearance and weather resistance. When the content of the silane monomer having an alkoxy group is less than the range described above, the number of siloxane bonds is small, and thus the cross-linking density is reduced, thereby reducing the adhesion, gloss and durability of the coating film. When it exceeds the range described above, the increase in the molecular weight of the silane causes hydrolysis due to increased reactivity with moisture, resulting in reduced storage properties of the coating, and as a result, the appearance and scratch resistance of the coating film are reduced.

[0021] The silane-modified urethane acrylate oligomer can be produced by a method comprising reacting an acrylate monomer having a hydroxyl group with a silane monomer having an isocyanate group to prepare an intermediate, and then subjecting the intermediate to a hydrolysis and condensation reaction with the silane monomer having an alkoxy group. The reaction can be carried out in a solvent in the presence of a reaction catalyst.

[0022] Examples of the acrylate monomer having a hydroxyl group include 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, pentaerythritol triacrylate, and pentaerythritol tetraacrylate. These monomers may be used alone or in combination of two or more.

[0023] As the silane monomer having an isocyanate group, 3-isocyanatopropyltrimethoxysilane (IPTMS: (3-Isocyanatopropyl) (trimethoxy) silane), 3-isocyanatopropyltriethoxysilane, etc. can be used. These monomers can be used alone or in combination of two or more.

[0024] The silane monomer having an alkoxy group may include methyltrimethoxysilane, phenyltrimethoxysilane, tetramethoxysilane, tetraethoxysilane, methyltriethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, tetraethylorthosilicate, etc. These monomers may be used alone or in combination of two or more.

[0025] As the above-mentioned reaction catalyst, catalysts commonly used in the art can be used without limitation. As an example, dibutyl[bis(dodecanoyloxy)]stannane (DBTDL), acetic acid (1N Acetic acid in DIW), hydrochloric acid, etc. can be used.

[0026] As the above-mentioned solvent, solvents commonly used in this technical field can be used without limitation. As an example, methanol, ethanol, isopropanol, 2-methoxyethanol, 2-ethoxyethanol, 2-butoxyethanol, 1-methoxy-2-propanol (MOP: 1-Methoxy-2-propanol), etc. can be used.

[0027] The intermediate and the silane monomer having an alkoxy group are used in a weight ratio of 40 to 80:20 to 60, for example, 35 to 75:25 to 65. If the ratio of the intermediate to the silane monomer having an alkoxy group is less than the aforementioned range, the degree of crosslinking decreases, thereby reducing the adhesion of the coating film. If the ratio exceeds the aforementioned range, the crosslinking density increases, thereby reducing the elasticity of the coating film.

[0028] The silane-modified urethane acrylate oligomer may have a silsesquioxane structure. As an example, the silane-modified urethane acrylate oligomer may be represented by the following Chemical Formula 1.

[0029] [Chemical Formula 1]

[0030]

[0031] In the above formula,

[0032] Siloxane is a silsesquioxane.

[0033] PETA is Pentaerythritol triacrylate.

[0034] As an example, the siloxane is (RSiO 3 / 2 )n, which may be a silsesquioxane having a T-unit structure comprising a silicon atom bonded to three oxygen atoms, and may be synthesized using a hydrolysis-polycondensation method. For example, the siloxane may be polymerized from trialkoxysilane (RSi(OR)3) and trichlorosilane (RSiCl3), where R may be H, an alkyl group, an aryl group, or the like.

[0035] The silane-modified urethane acrylate oligomer having the above-mentioned silsesquioxane structure, when applied to black PC materials and transparent / black PC materials, has excellent coating storage stability and coating film adhesion due to its structural stability, and has excellent heat resistance, weather resistance and scratch resistance of the coating film due to the siloxane bond.

[0036] The UV-curable coating composition comprises the silane-modified urethane acrylate oligomer in an amount of 5 to 15% by weight, for example, 7 to 13% by weight, based on the total weight of the coating composition. If the content of the silane-modified urethane acrylate oligomer is less than the aforementioned range, the crosslink density of the resulting coating film decreases, thereby reducing hardness, chemical resistance, and adhesion. If the content exceeds the aforementioned range, the viscosity of the coating increases excessively, thereby reducing workability and drying properties, resulting in poor appearance and processability of the coating film.

[0037] Polyurethane acrylate oligomer

[0038] The ultraviolet curable coating composition of the present invention comprises a urethane acrylate oligomer, which may comprise a 4- to 6-functional urethane acrylate oligomer and a 2- to 3-functional urethane acrylate oligomer.

[0039] The 4- to 6-functional urethane acrylate oligomers improve the hardness and scratch resistance of the coating composition. The weight-average molecular weight of the 4- to 6-functional urethane acrylate oligomers is 2,000 to 4,000 g / mol, for example, 1,500 to 3,500 g / mol. If the weight-average molecular weight is below the aforementioned range, the coating viscosity is low, resulting in reduced adhesion and gloss of the coating film. If the weight-average molecular weight exceeds the aforementioned range, the crosslink density increases significantly, reducing the elasticity of the coating film and resulting in cracks, which can reduce the appearance and scratch resistance.

[0040] The bifunctional to trifunctional urethane acrylate oligomer improves the adhesion and wear resistance of the coating composition. The weight-average molecular weight of the bifunctional to trifunctional urethane acrylate oligomer is 1,000 to 3,000 g / mol, for example, 1,500 to 2,500 g / mol. If the weight-average molecular weight is below the aforementioned range, the coating viscosity is low, resulting in reduced adhesion and gloss of the coating film. If the weight-average molecular weight exceeds the aforementioned range, the crosslinking density increases significantly, reducing the elasticity of the coating film and resulting in cracks, which can reduce the appearance and scratch resistance.

[0041] The UV-curable coating composition comprises the polyurethane acrylate oligomer in an amount of 15 to 35% by weight, for example, 20 to 30% by weight, based on the total weight of the coating composition. If the content of the polyurethane acrylate oligomer is less than the aforementioned range, the crosslink density of the resulting coating film decreases, thereby reducing hardness, chemical resistance, and adhesion. If the content exceeds the aforementioned range, the viscosity of the coating increases excessively, thereby reducing workability and drying properties, resulting in reduced appearance and workability of the coating film.

[0042] As an example, the UV-curable coating composition comprises 10 to 20% by weight, for example, 13 to 18% by weight, of the 4- to 6-functional urethane acrylate oligomer, and 5 to 15% by weight, for example, 7 to 13% by weight, of the 2- to 3-functional urethane acrylate oligomer, based on the total weight of the coating composition. If the content of the 4- to 6-functional urethane acrylate oligomer is below the aforementioned range, the crosslink density of the resulting coating film decreases, leading to reduced mechanical properties and adhesion. If the content exceeds the aforementioned range, the viscosity of the coating increases excessively, resulting in reduced workability and drying properties, resulting in a reduced appearance of the coating film. If the content of the 2- to 3-functional urethane acrylate oligomer is below the aforementioned range, the crosslink density of the resulting coating film decreases, leading to reduced hardness, chemical resistance, and adhesion. If the content exceeds the aforementioned range, the viscosity of the coating increases excessively, leading to reduced workability and drying properties, resulting in a reduced appearance and processability of the coating film.

[0043] Acrylate monomer

[0044] The UV-curable coating composition of the present invention contains an acrylate monomer. The acrylate monomer may include a monofunctional to trifunctional acrylate monomer. The acrylate monomer plays a role in improving the main physical properties of the coating film other than adhesion.

[0045] Non-limiting examples of the above-mentioned acrylate monomers include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and isobornyl (meth)acrylate. These can be used alone or in combination of two or more.

[0046] The UV-curable coating composition comprises the acrylate monomer in an amount of 10 to 25% by weight, for example, 15 to 20% by weight, based on the total weight of the coating composition. If the acrylate monomer content is less than the aforementioned range, drying properties may be reduced, thereby decreasing adhesion and durability of the coating film. If the content exceeds the aforementioned range, the coating viscosity may decrease, thereby decreasing coating workability and paint fluidity of the coating composition.

[0047] Photoinitiator

[0048] The UV-curable coating composition of the present invention includes a photoinitiator. Examples of the photoinitiator include 1-hydroxycyclohexylphenyl ketone and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, which can be used alone or as a mixture of two or more. The photoinitiator may include two or more photoinitiators having different effective absorption wavelengths.

[0049] The UV-curable coating composition may contain the photoinitiator in an amount of 1 to 6 weight percent, for example, 1.1 to 5.5 weight percent, based on the total weight of the coating composition. If the photoinitiator content is less than the aforementioned range, the curability may be reduced or the coating may not be cured, resulting in reduced strength and adhesion of the coating film or wrinkles. If the content exceeds the aforementioned range, unreacted photoinitiator may cause contamination, and overcuring may result in reduced appearance and reflectivity.

[0050] As an example, the above-mentioned UV-curable coating composition contains 1 to 5 weight % of 1-hydroxycyclohexyl phenyl ketone, for example, 2 to 4 weight % based on the total weight of the coating composition, and contains 0.1 to 1 weight % of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, for example, 0.2 to 0.9 weight %.

[0051] organic solvents

[0052] The ultraviolet curable coating composition of the present invention may contain an organic solvent. The organic solvent is not particularly limited as long as it can improve the solubility of the coating and lower the viscosity to improve workability.

[0053] As the organic solvent, ketone solvents, ester solvents, ether solvents, alcohol solvents, or mixtures thereof can be used. Non-limiting examples of the organic solvent include propylene glycol methyl ether, toluene, xylene, methyl ethyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isobutyl ketone, ethyl propyl ketone, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, butyl acetate, methyl cellosolve acetate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, methanol, ethanol, n-propanol, isopropyl alcohol, n-butanol, isobutyl alcohol, tert-butanol, benzene, acetone, tetrahydrofuran, dimethylformaldehyde, and cyclohexanone. These can be used alone or in combination of two or more.

[0054] The content of the organic solvent is not particularly limited and may be a residual amount adjusted to bring the total weight of the coating composition to 100%. For example, the UV-curable coating composition may contain 30 to 60% by weight of the organic solvent based on the total weight of the coating composition.

[0055] additive

[0056] The ultraviolet curable coating composition of the present invention may further contain one or more additives commonly used in the art, such as an ultraviolet absorber, an ultraviolet stabilizer, a flame retardant, a leveling agent, and a defoaming agent.

[0057] As ultraviolet absorbers, hydroxyphenyl triazine (HPT) derivatives can be used, as ultraviolet stabilizers, amine light stabilizers (HALS: Hindered Amine Light Stabilizers) can be used, as antioxidants, phenolic compounds can be used, as leveling agents, silicone diacrylates, silicone polyacrylate compounds can be used, and as defoaming agents, dimethyl polysiloxane can be used.

[0058] The content of the above additives is not particularly limited, and for example, each may be 0.1 to 10 wt % based on the total weight of the coating composition.

[0059] The present invention will be described in more detail below by way of examples. However, the following examples are provided only to facilitate understanding of the present invention, and the scope of the present invention is not limited to the examples in any sense.

[0060] [Synthesis Example 1: Synthesis of Silane-Modified Urethane Acrylate Oligomer]

[0061] After preparing a reactor equipped with a thermometer, a stirrer, a reflux cooler, an air injection system, and a nitrogen injection system, 0.1g of a polymerization inhibitor (butylated hydroxytoluene), 226g of monomer 1-1 (PETA 70%), and 78g of monomer 2 (3-isocyanatepropyltrimethoxysilane) were added to the reactor while nitrogen was added. The temperature was raised to 40°C while stirring. At 40°C, 0.1g of reaction catalyst 1 (dibutyltin dilaurate) was added, and while confirming heat generation, the temperature was raised to 60°C and maintained for 5 hours. The reaction was then continued until the NCO% reached 0.05% or less as measured by wet NCO% measurement. The reaction was terminated when the NCO% met the requirements, yielding an intermediate. The prepared intermediate had a solids content of 100% and a viscosity (25°C) of 600 cps.

[0062] After preparing a reactor equipped with a thermometer, a stirrer, a reflux cooler, an air injection system, and a nitrogen injection system, 304 g of the intermediate prepared above, 105 g of monomer 3-1 (ethyl orthosilicate), 105 g of monomer 3-2 (methyltrimethoxysilane), and 420 g of solvent (propylene glycol methyl ether) were added to the reactor while nitrogen was added. The temperature was raised to 35°C. Once the temperature reached 35°C, 11 g of reaction catalyst 2 (1N acetic acid) and 54.8 g of DIW were added. After maintaining the temperature for one hour while paying attention to heat generation, the temperature was raised to 60°C and maintained for 15 hours. The solid content was measured and the yield was confirmed to be at least 95%. The reaction was then terminated to obtain silane-modified urethane acrylate oligomer 1. The solid content of the prepared silane-modified urethane acrylate oligomer 1 was 37% and the viscosity (25°C) was 15 cps.

[0063] [Synthesis example 2-19]

[0064] Oligomers of Synthesis Examples 2 to 19 were prepared in the same manner as Synthesis Example 1, except that the compositions were as described in Tables 1 to 3 below.

[0065] [Table 1]

[0066]

[0067] [Table 2]

[0068]

[0069] [Table 3]

[0070]

[0071]

[0072] Monomer 1-1: Pentaerythritol triacrylate 70%, Pentaerythritol tetraacrylate 30%

[0073] Monomer 1-2: Pentaerythritol triacrylate

[0074] Monomer 2: 3-isocyanatopropyltrimethoxysilane

[0075] Monomer 3-1: Tetraethyl orthosilicate

[0076] Monomer 3-2: Methyltrimethoxysilane

[0077] Reaction catalyst 1: Dibutyl[bis(dodecanoyloxy)]stannane (DBTDL)

[0078] Reaction catalyst 2: 1N acetic acid

[0079] Inhibitor: 2,6-bis(1,1-dimethylethyl)-4-methylphenol (BHT(2,6-bis(1,1-dimethylethyl)-4-methylphenol))

[0080] Solvent: 1-methoxy-2-propanol

[0081] [Examples 1-10: Preparation of UV-curable coating compositions]

[0082] The ultraviolet curable coating composition of each example was prepared according to the composition described in Table 4 below.

[0083] [Comparative Example 1-9: Preparation of UV-curable coating composition]

[0084] The ultraviolet curable coating composition of each comparative example was prepared according to the composition described in Table 5 below.

[0085] [Table 4]

[0086]

[0087] [Table 5]

[0088]

[0089] Oligomer 1-1: Silane-modified urethane acrylate oligomer of Synthesis Example 1 Oligomer 1-2: Silane-modified urethane acrylate oligomer of Synthesis Example 2 Oligomer 1-3: Silane-modified urethane acrylate oligomer of Synthesis Example 3 Oligomer 1-4: Silane-modified urethane acrylate oligomer of Synthesis Example 4 Oligomer 1-5: Silane-modified urethane acrylate oligomer of Synthesis Example 5 Oligomer 1-6: Silane-modified urethane acrylate oligomer of Synthesis Example 6 Oligomer 1-7: Silane-modified amino acrylate oligomer of Synthesis Example 7 Oligomer 1-8: Silane-modified urethane acrylate oligomer of Synthesis Example 8 Oligomer 1-9: Silane-modified urethane acrylate oligomer of Synthesis Example 9 Oligomer 1-10: Silane-modified urethane acrylate oligomer of Synthesis Example 10 Oligomer 1-11: Silane-modified urethane acrylate oligomer of Synthesis Example 11 Oligomer 1-12: Silane-modified urethane acrylate oligomer of Synthesis Example 12 Oligomer 1-13: Silane-modified urethane acrylate oligomer of Synthesis Example 13

[0090] Oligomer 1-14: Silane-modified urethane acrylate oligomer of Synthesis Example 14

[0091] Oligomer 1-15: Silane-modified urethane acrylate oligomer of Synthesis Example 15

[0092] Oligomer 1-16: Silane-modified urethane acrylate oligomer of Synthesis Example 16

[0093] Oligomer 1-17: Silane-modified urethane acrylate oligomer of Synthesis Example 17

[0094] Oligomer 1-18: Silane-modified urethane acrylate oligomer of Synthesis Example 18

[0095] Oligomer 1-19: Silane-modified urethane acrylate oligomer of Synthesis Example 19

[0096] Oligomer 2: 6-functional urethane acrylate oligomer (Mw 2,400 g / mol, viscosity (25°C) 4,780 cps, Nv 80 wt%)

[0097] Oligomer 3: trifunctional urethane acrylate oligomer (Mw 1,200 g / mol, viscosity (25°C) 1,900 cps, NV 82 wt%)

[0098] Monomer 1: 1,6-Hexamethylene diacrylate

[0099] Monomer 2: Trimethylolpropane triacrylate

[0100] Photoinitiator 1: 1-Hydroxycyclohexylphenyl ketone

[0101] Photoinitiator 2: Bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide

[0102] UV absorber: Hydroxyphenyl Triazines (HPT)

[0103] UV stabilizer: TINUVIN123, BASF

[0104] Antioxidant: SONGNOX 1076, SONGWON, South Korea

[0105] Silicone additive: BYK-333, BYK (BYK Chemical)

[0106] Organic solvent: a mixture of toluene, ethyl acetate, butyl acetate, KOCOSOL #100, xylene, and methyl isobutyl ketone

[0107] [Physical property evaluation]

[0108] In order to measure the physical properties of the coating films formed using the ultraviolet curable coating compositions prepared in the respective experimental examples, physical property tests were conducted according to the following physical property measurement methods. The results are shown in Tables 6 and 7 below.

[0109] Test piece production

[0110] The UV curable coating composition prepared in each experimental example was coated on a polycarbonate substrate (thickness: 20 μm) and photocured (IR before curing: 50° C. × 3 minutes, light intensity: 1,000 mJ / cm 2 , light intensity: 170mW / cm 2 ) to form a coating film.

[0111] Initial adhesion

[0112] A cross-cut tape test was performed and evaluated according to ASTM D3359. A cross cutter was used to create 100 scratches (10 horizontal and 10 vertical) measuring 1 mm x 1 mm on the surface. Nichiban tape was applied and then removed. The number of scratches that retained the coating film was counted to evaluate adhesion.

[0113] [Evaluation Criteria]

[0114] Excellent (◎): Coating adhesion maintains more than 99 grids

[0115] Good (○): Coating adhesion is maintained at more than 95 grids and less than 99 grids

[0116] General (△): Coating adhesion is maintained at more than 85 grids and less than 95 grids

[0117] Poor (×): Coating adhesion is less than 85 grids

[0118] Heat resistance

[0119] The test pieces were placed at the test temperature (120°C) for 10 days, then taken out and placed at room temperature for 1 hour. The coating was then observed for discoloration, fading, swelling, cracking, gloss reduction, and peeling, and evaluated as excellent (◎), good (○), fair (△), and poor (×).

[0120] Water resistance

[0121] The test pieces were placed in water at the test temperature (40°C) for 10 days, then taken out and placed at room temperature for 1 hour. The coating was observed for discoloration, fading, swelling, cracking, gloss reduction, and peeling, and evaluated as excellent (◎), good (○), fair (△), and poor (×).

[0122] Moisture resistance

[0123] After the test pieces were left at 45°C and 95% RH for 10 days, the coatings were observed for discoloration, fading, swelling, cracking, gloss reduction, and peeling, and were evaluated as excellent (◎), good (○), fair (△), and poor (×).

[0124] Thermal shock

[0125] The test pieces were placed at a test temperature (-40°C to 80°C), then taken out and left at room temperature for 1 hour. The coating was then observed for discoloration, fading, swelling, cracking, gloss reduction, and peeling, and evaluated as excellent (◎), good (○), fair (△), and poor (×).

[0126] Heat and cold resistance

[0127] After the test piece was placed at a temperature of -20°C and a humidity of 95% RH for 4 hours, the temperature and humidity conditions were changed to 40°C and 95% RH, respectively, and then placed under these conditions for 4 hours. This series of processes was repeated 5 times, and then placed at room temperature for 1 hour. The discoloration, fading, swelling, cracking, gloss reduction, peeling, etc. of the coating were observed and evaluated as excellent (◎), good (○), fair (△), and poor (×).

[0128] Promote weather resistance

[0129] After irradiating each test piece under the following xenon arc furnace conditions according to SAE J1960, the coating was observed for noticeable discoloration [color difference (ΔE*): 3.0 or less], fading, swelling, cracking, gloss reduction, and other abnormalities in adhesion. Evaluations were performed using a scale of excellent (◎), good (○), fair (△), and poor (×).

[0130] Xenon arc furnace setting conditions: 4,000kJ / m 2 [340nm], BLACK PNL temperature (LIGHT) -38±2℃ (DARK) irradiation 40 minutes (50±5%RH), cycle - irradiation 60 minutes (50±5%RH) non-irradiation 60 minutes (95±5%RH), irradiation illumination -0.55±0.02W / (m 2 nm)[340nm]

[0131] [Table 6]

[0132]

[0133] [Table 7]

[0134]

[0135] As shown in Tables 6 and 7 above, the coating compositions of Examples 1 to 10 using the silane-modified urethane acrylate oligomers (Oligomers 1-1 to 1-10) according to the present invention exhibited excellent physical properties across all measured items. In contrast, the coating compositions of Comparative Examples 1 to 6 using silane-modified urethane acrylate oligomers (Oligomers 1-11 to 1-16) containing three monomers but in amounts outside the content range of the present invention, the coating composition of Comparative Example 7 using a silane-modified urethane acrylate oligomer (Oligomer 1-17) not containing an acrylate monomer having a hydroxyl group, the coating composition of Comparative Example 8 using a silane-modified urethane acrylate oligomer (Oligomer 1-18) not containing an isocyanate group, and the coating composition of Comparative Example 9 using a silane-modified urethane acrylate oligomer (Oligomer 1-19) not containing an alkoxy group exhibited inferior physical properties compared to the coating compositions of Examples 1 to 10.

[0136] (Industrial Applicability)

[0137] The present invention provides an ultraviolet curable coating composition having excellent curing stability, adhesion and weather resistance, and a silane-modified urethane acrylate oligomer applicable thereto.

Claims

1. A silane-modified urethane acrylate oligomer prepared from a composition comprising an acrylate monomer having a hydroxyl group, a silane monomer having an isocyanate group, and a silane monomer having an alkoxy group, Based on the total weight of the composition, the silane-modified urethane acrylate oligomer comprises 10 to 33 wt % of an acrylate monomer having a hydroxyl group, 3 to 12 wt % of a silane monomer having an isocyanate group, and 7 to 35 wt % of a silane monomer having an alkoxy group. 2 . The silane-modified urethane acrylate oligomer according to claim 1 , having a number average molecular weight of 500 to 10,000 g / mol and an acrylic acid equivalent weight of 100 to 1,000 g / eq.

3. The silane-modified urethane acrylate oligomer according to claim 1, wherein The silane-modified urethane acrylate oligomer is prepared by the following method, which includes the steps of reacting an acrylate monomer having a hydroxyl group and a silane monomer having an isocyanate group to prepare an intermediate, and subjecting the intermediate to a hydrolysis and condensation reaction with a silane monomer having an alkoxy group.

4. The silane-modified urethane acrylate oligomer according to claim 3, wherein The mixing ratio of the intermediate and the silane monomer having an alkoxy group is 40 to 80:20 to 60 by weight.

5. The silane-modified urethane acrylate oligomer according to claim 1, wherein The silane-modified urethane acrylate oligomer is represented by the following Chemical Formula 1: [Chemical Formula 1] In the above formula, Siloxane is a silsesquioxane. PETA is pentaerythritol triacrylate.

6. A UV-curable coating composition comprising a silane-modified urethane acrylate oligomer, a polyurethane acrylate oligomer, an acrylate monomer, and a photoinitiator, The silane-modified urethane acrylate oligomer is the silane-modified urethane acrylate oligomer according to any one of claims 1 to 5.

7. The ultraviolet curable coating composition according to claim 6, wherein The above-mentioned urethane acrylate oligomer comprises 4 to 6 functional urethane acrylate oligomer and 2 to 3 functional urethane acrylate oligomer, The weight average molecular weight of the 4- to 6-functional urethane acrylate oligomer is 2,000 to 4,000 g / mol. The 2- to 3-functional urethane acrylate oligomer has a weight average molecular weight of 1,000 to 3,000 g / mol.

8. The ultraviolet curable coating composition according to claim 6, wherein Based on the total weight of the coating composition, the coating composition comprises 5 to 15 weight % of the silane-modified urethane acrylate oligomer, 15 to 35 weight % of the polyurethane acrylate oligomer, 10 to 25 weight % of the acrylate monomer, and 1 to 6 weight % of the photoinitiator.

Citation Information

Patent Citations

  • UV curable blend compositions and the process of their use and coated articles resulting therefrom

    KR100199908B1